Quality of earnings and normative characteristics: Views from C-suite - Makhaiel, Nargis kaisar boles (Journal of Accounting and Investment, 2025)
Research aims: This research aims to explore the effect of normative attributes of the top management team (TMT) on the quality of earnings figures.Design/Methodology/Approach: The research drew on an interpretive approach and semi-structured interviews conducted with thirty-three members of top management from nine different sectors.Research findings: The findings reveal that, within the Egyptian setting, the quality of earnings is a product of the combined and overlapping effect of the TMT’s normative characteristics. These personal features are dominated by the utilitarian ethical orientation, which is based on the collectivist nature of Egyptian society.Theoretical contribution/originality: This study’s contributions to the literature include supporting the theory advocating that the quality of financial disclosure is an outcome of a joint set of normative motivators, including the TMT’s demographic, cultural, and ethical traits; suggesting the importance of considering the quality of earnings as a multifaceted task, as there is no one normative characteristic working in isolation from others. Also, this survey advances academic’s understanding of the upper echelons (UE) theory by choosing Egypt, a non-U.S. and non-developed setting, as a research context that faces scarce research in this area. Practitioner/Policy implications: Conceptualising the relationship between the transparency of FRs and TMT’s normative profile in the Egyptian context might be of assistance to diversified interested parties such as policymakers, regulators, stakeholders, global markets, organisations, external auditors, scholars, the accounting profession, and academics Research limitation\implication: The research ignored fields like financial and banking fields, and the findings may not be equally applicable to other settings rather than Egypt.